On exports and economic growth - Izani Ibrahim, (Penerbit Universiti Kebangsaan Malaysia, 2002)
This paper focuses on a new estimate of Feder (1982)’s model on productivity and externality effect of exports in six Asian countries. Econometric issues are addressed with the use of cross-sectional analysis. The results show that the coefficients of the models reduce substantially when the analysis is adjusted for stationarity. The effect of exports on growth and productivity is found to be positively significant and the export sector is found to have a positive effect on non-export sector. However, the extent of externality effect will depend on several factors such as size, policy orientation of exports, concentration of export products and processing level of exports